The carbon reduction potential by improving technical efficiency from energy sources to final services in China: An extended Kaya identity analysis. (15th January 2023) - Lin, Yuancheng; Ma, Linwei; Li, Zheng; Ni, Weidou
Abstract: Improving energy efficiency is one of the most reliable ways toward carbon neutrality. Most previous studies have focused on how to reduce energy intensity; however, it is not enough to provide an overview of how many carbon emissions can be reduced by technical efficiency improvements underlying energy systems. To fill this gap, this study extended the common Kaya identity to systematically evaluate the carbon reduction potential from technical efficiency improvements of various technical conversion components within the energy system at a granular level. The extended Kaya identity includes technical efficiency factors of electricity efficiency, conversion efficiency, and passive efficiency. It provides a comprehensive framework to evaluate current performance, historical contributions, and future potential of technical efficiency improvements. The case of China reveals that: Currently, only around 5% of energy sources were delivered to final services. By improving technical efficiency to high levels, 59% carbon reduction can be achieved during the future energy transition, even when the economy is still growing. In the past, electricity efficiency and conversion efficiency have significantly reduced carbon emissions. Future policymakers should pay more attention to passive systems to provide more final services, such as improved room insulation, streamlined vehicle designs, and smart energy management. Highlights: Proposed an extended Kaya identity framework for the systematic evaluation. Evaluated the role of technical efficiency improvements at the most granular level. 59% carbon reduction by improving technical efficiency during energy transition. Passive systems highlighted for more carbon reduction potential. Strongly promoting technical efficiency improvements in China's carbon neutrality.